KONSEP SISTEM INFORMASI MANAJEMEN DAKWAH - Erwan Effendy; Juwita Yanti Panggabean; Den Bagus Pangestu (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Data and information are different but the concepts are related.Data is the raw material from which information is produced,fromal information is differentiated and informal information is the result of the legitimacy information system. A system is a set of objects and the relationships between these objects arranged for a coomon goal. Information systems can be the idea of a the series of files created stating the source of information is often termed a project.The project can be viewed as a circle of life which in the case of an information system can be divide into four phases.